All Days 2014
DOI: 10.2118/168024-ms
|View full text |Cite
|
Sign up to set email alerts
|

Degradable Fiber Pill for Lost Circulation in Fractured Reservoir Sections

Abstract: Lost circulation is one of the main causes of nonproductive time during drilling and impacts the success of cementing operations. Losses into the reservoir not only impact drilling, they potentially impact the reservoir, due to influx of quantities of drilling fluids that are potentially damaging, or will influence the production rate. Existing solutions are based mainly on particulates, which often are added to drilling fluids to plug fractures or to build up filtercake to cure fluid losses. When particulates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Priening et al [25] reported that the advanced engineering fibers composed of inert material are easy to disperse in the drilling fluid and can make a 3D network across the loss zone, thereby allowing the solids in the drilling fluid to form bridging plug and cure the losses. According to Droger et al [26], the performance of fiber LCM is affected by fiber concentration, fluid viscosity, fiber geometry, fracture width, and flow rate. They concluded that degradable fiber systems are effective for preventing losses in fractures as wide as 5 mm.…”
Section: Lost Circulation Materialsmentioning
confidence: 99%
“…Priening et al [25] reported that the advanced engineering fibers composed of inert material are easy to disperse in the drilling fluid and can make a 3D network across the loss zone, thereby allowing the solids in the drilling fluid to form bridging plug and cure the losses. According to Droger et al [26], the performance of fiber LCM is affected by fiber concentration, fluid viscosity, fiber geometry, fracture width, and flow rate. They concluded that degradable fiber systems are effective for preventing losses in fractures as wide as 5 mm.…”
Section: Lost Circulation Materialsmentioning
confidence: 99%
“…Natural Fibers Natural fibers (Droger et al 2014;Mukherjee andKao 2011, Driscoll et al 2013;Fuqua et al 2012;Gupta and Kumar 2012;Hughes 2012;Fidelis et al 2014) have been widely used in the oil and gas industry for applications in lost-circulation curing. Fiber technology can enhance the mechanical properties of the bridge.…”
Section: Reservoir-friendly Lcm For Wellbore Strengtheningmentioning
confidence: 99%
“…The addition of these components to fluid formulations can increase the viscoelastic properties, enhancing the ability to sustain pressures and temperatures (Lécolier et al 2005). Acid treatments can react with the carbonate reservoir creating large wormholes and reducing the efficiency of the treatment (Droger et al 2014). However, they cannot always be removed, causing severe permeability damage (Samuel et al 2003).…”
Section: Natural Fibersmentioning
confidence: 99%
See 2 more Smart Citations